Loudspeaker handbook - Eargle, John (Chapman & Hall, 1997)
The second edition of Loudspeaker Handbook follows the same general outlines as the highly successful first edition and has been augmented and updated in many areas of technology. Most notable are the developments in large-scale, programmable line arrays, distributed mode loudspeakers, and ultrasonic-based audio transduction. Additionally, the core chapters on low frequency systems, system concepts, and horn systems have been expanded to include both more analytical material and a richer array of examples. Much of the success of the first edition has been due to its accessibility both to loudspeaker engineers and to lay technicians working in the field - a point of view the author maintains in the present work. A full understanding of the underlying technology requires a fairly rigorous engineering background through the second year of professional study. At the same time, the generous use of graphs, with their intuitive thrust, will be useful to all readers. Loudspeaker Handbook, Second Edition continues to be appropriate for use in courses at the undergraduate senior level, for graduate students, and for professionals in audio and acoustical engineering.